Evolutionary Multi-Criteria Optimization (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Reprint compiles all articles accepted and published in the Special Issue of Mathematics entitled "Evolutionary Multi-Criteria Optimization: Methods and Applications". This Special Issue seeks to bring together both experts and newcomers to explore emerging and existing issues in these domains, with a particular focus on advancing the integration and synthesis of ideas between EMO and MCDM researchers. By fostering such collaboration, this collection seeks to enhance engagement with the user community and promote practical applications of these methodologies. We hope that the papers featured in this Special Issue will be of interest to our readers.